An Analysis of Students’ Critical Reading Skills: A Study in Indonesian Tertiary Education - Munir (Har Press Indonesia, 2025)
This study is descriptive qualitative research that aims to determine the extent of students' reading skills, namely their ability to analyses, synthesize, and evaluate texts. The population of this study was all second-semester students of the 2022/2023 academic year in the English Department of Makassar State University. The subjects of the study were 20 students from class 01 of the English Education Study Program 2022/2023. The data were obtained through the reading test. The results showed that the three aspects of critical reading - analyzing synthesizing, and evaluating were the easiest for the students. However, the results also showed a growing ability to recognize the author's intention and identify the underlying assumptions. Besides, there is still room for improvement in critical thinking, especially in areas such as analytical techniques, evaluating bias, and considering alternative perspectives.